Pemanfaatan limbah biji mangga menjadi minyak nabati dengan proses ekstraksi - Manik, Natalia; Masrida, Reni (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The extraction process is a process of separating a substance based on its dissolution difference against two different dissolved liquids, usually water and the other an organic solvent. Vegetable oil is an oil that can be extracted from various parts of the plant that is processing the stems, leaves, seeds, flowers and fruit peel. Seed is one of the main ways plants to regenerate. Seeds contain large and distinct quantities of macromolecule reserves, which are stored as a source of spare food to support early germination. As an alternative to the healthful drugs of the body from various diseases that will attack the human body and have other important benefits. In this study used an extraction research method that produced vegetable oils in using 30 grams of mango seeds each on a 6-time process with ethanol and hexane solvents which used 500 ml each at a given time. From a good yield yield obtained at 3 hours of extraction process with ethanol solvent having a yield of 50%, then having a good quality is obtained by the yield of vegetable oil by using ethanol solvent. Thus the vegetable oils of the extraction process have a good oil content in the ethanol solvent versus hexane.